Creation of Farms in the Southern Regions of Uzbekistan and its Results - Botirova Halima Eshmamatovna (International Journal on Human-Computing Studies, 2021)
This article is devoted to the protection of the interests of agricultural specialists, employees and workers in the agricultural sector, which is an important part of the ongoing economic reforms in the country. As a result of agrarian reforms, farms began to be created in the country. The purpose of creating farms is to use the experience of developed countries with extensive experience in the agricultural sector to introduce innovations and increase economic interest.